Wave propagation: a finite difference modelling in a 3D fluid-solid configuration. - Contreras, Xiomara; Aldana, Milagrosa (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this work, the behavior of a wave field in a 3D solid-fluid configuration has been modeled. The elastodynamic equations that describe the problem were expressed, independently, in terms of both dis- placement-stress (EDE) and velocity-stress (EVE). Both systems were solved using a staggered-grid Finite Difference approach (SFD). A horizontal and an inclined surface were considered. In the first case, a transitional zone was used to solve the discontinuity at the interface. The other case introduces the medium heterogeneity into the grid, point by point, by means of the Lamé parameters and the density values. Our results indicate, for the first strategy, an increase in the amplitudes of the refractions and reflections; however, it does not modify the correct understanding of the geological model. The second strategy does not aggregate numerical effects to the results, but it could be unsuccessful in the presence of an irregular interface. Nevertheless, both strategies can be appropriate to solve basic 3D fluid-solid interface problems.